2021
DOI: 10.3390/su13063262
|View full text |Cite
|
Sign up to set email alerts
|

A Systemic Review on Microalgal Peptides: Bioprocess and Sustainable Applications

Abstract: Nowadays, microalgal research is predominantly centered on an industrial scale. In general, multipotent bioactive peptides are the advantages over focal points over utilitarian nourishment as well as nutraceuticals. Microalgal peptides are now profoundly connected with biological properties rather than nutritive. Numerous techniques are employed to purify active peptides from algal protein using enzymatic hydrolysis; it is broadly used for numerous favorable circumstances. There is a chance to utilize microalg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 122 publications
(152 reference statements)
0
14
0
Order By: Relevance
“…Ultrafiltration and gel filtration chromatography were used for the purification of protein hydrolysates prepared by Alcalase 2.4 L. The LMWF displayed better activity on scavenging DPPH radicals than the HMWF ( Figure 2 ). Previous studies have proven that amino acid residues ranging from 5–11 showed good antioxidant activities [ 34 , 35 ]. The LMWF was further purified using the Sephadex G-25 chromatography to obtain two fractions named F-A and F-B.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrafiltration and gel filtration chromatography were used for the purification of protein hydrolysates prepared by Alcalase 2.4 L. The LMWF displayed better activity on scavenging DPPH radicals than the HMWF ( Figure 2 ). Previous studies have proven that amino acid residues ranging from 5–11 showed good antioxidant activities [ 34 , 35 ]. The LMWF was further purified using the Sephadex G-25 chromatography to obtain two fractions named F-A and F-B.…”
Section: Resultsmentioning
confidence: 99%
“…Even though numerous anticancer peptides have been thoroughly described and their activity has been demonstrated, their use may be limited by their rapid kidney and liver clearance [193], protease degradation by hydrolysis [194], or instability in gastrointestinal tract [195] or body fluids, such as blood [196].…”
Section: Disadvantages Of Peptides Targeting Cancer Cellsmentioning
confidence: 99%
“…[10 -11] They also exhibit anti-hypertensive, immune-modulatory, anti-cancer, hepatoprotective, anti-atherosclerotic, anticoagulant, anti-UV radiation, anti-osteoporosis and anti-microbial activities. [12] As food ingredients, amino acids glutamic and aspartic acids contribute to enhance food flavour of meat, soy sauce, seafood and some processed food. [13 -14] Besides, supplementation with glutamic acid could be advantageous due to its beneficial effects in: (i) protecting intestinal function from the oxidative stress, (ii) regulating the intestinal damage cause by mycotoxins, (iii) lowering blood pressure, (iv) reducing cardiovascular disease risk, (v) increasing the efficacy and decreasing the toxicity of anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins are one of the main components of microalgae, reaching up to 70 % of dry biomass and containing up to 50 % of essential amino acids, with higher antioxidant capacities compared to common proteins in human diet [10–11] . They also exhibit anti‐hypertensive, immune‐modulatory, anti‐cancer, hepatoprotective, anti‐atherosclerotic, anticoagulant, anti‐UV radiation, anti‐osteoporosis and anti‐microbial activities [12] …”
Section: Introductionmentioning
confidence: 99%